Performance of Islamic stocks versus conventional stocks during crisis and non crisis period: Evidence from MENA region. - Abou El Enein, Eshraq (AUC Knowledge Fountain, 2020)
The purpose of this thesis is to examine the performance of both Islamic and conventional stocks, and to investigate whether the Islamic filtering criteria acts as a shield of protection for investors during crisis or not, based on a panel sample of 12 countries in the MENA region covering 10 different sectors from 1998-2018. Using panel fixed effect regression. We divided out sample into three periods; 1998-2006 pre-crisis period, 2007-2008 crisis period and 2009-2018 post crisis period. Our main finding is that the filtering criteria has a positive relation with the returns significant for the post crisis period and positive significance for the two other periods; crisis and pre crisis.